2014
DOI: 10.1002/hipo.22346
|View full text |Cite|
|
Sign up to set email alerts
|

The role of postnatal neurogenesis in supporting remote memory and spatial metric processing

Abstract: In this study, we determined the contribution of juvenile neurogenesis to the performance of mice on a remote memory for temporally based association task and in a novelty based spatial pattern separation task. This was accomplished by mating homozygous DNMT1‐loxP mice with heterozygous GFAP‐Cre mice and comparing Cre+ (no postnatal neurogenesis) to Cre− (wild type) littermate offspring. The results indicate that Cre+ mice are impaired relative to Cre− mice in the remote memory for a temporal based association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…Hippocampal neurogenesis is required for spatial memory Kesner et al, 2014) and a reduction in cell proliferation, which is needed for hippocampal neurogenesis, has been associated with spatial memory deficits caused by VPA , ischemic stroke (Li et al, 2009), chemotherapy drugs (ElBeltagy et al, 2010Lyons et al, 2012;Lyons et al, 2011;, irradiation (Madsen et al, 2003; or stress . Fluoxetine enhances hippocampal neurogenesis and has been shown to have neuroprotective properties Lyons et al, 2012;Lyons et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal neurogenesis is required for spatial memory Kesner et al, 2014) and a reduction in cell proliferation, which is needed for hippocampal neurogenesis, has been associated with spatial memory deficits caused by VPA , ischemic stroke (Li et al, 2009), chemotherapy drugs (ElBeltagy et al, 2010Lyons et al, 2012;Lyons et al, 2011;, irradiation (Madsen et al, 2003; or stress . Fluoxetine enhances hippocampal neurogenesis and has been shown to have neuroprotective properties Lyons et al, 2012;Lyons et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, various studies have indicated that non-hippocampus-dependent learning does not require adult neurogenesis 4246 (but see also REFS 4751). In line with a role for young adult-born neurons in novelty encoding and learning, navigating in novel and enriched environments also increases adult neurogenesis 23,52,53 .…”
Section: Dentate Gyrus Functionmentioning
confidence: 99%
“…It remains to be determined how the different functional cell types may play distinct roles in these mnemonic processes. A particularly critical question concerns the role of adult neurogenesis in the functions of the DG (Nakashiba et al, 2012; Frankland, Kohler, & Josselyn, 2013; Akers et al, 2014; Kesner et al, 2014). The DG data presented here come from all cells in the DG that met certain spatial information criteria.…”
Section: Final Comments and Caveatsmentioning
confidence: 99%